Organizing hematologic gene sequence data using neighbor joining phylogeny method - J. Bipin Nair, B (International Journal of Engineering and Technology, 2018)
There are a number of methods to spot orthologous genes from homologous genes. Since identifying orthologous genes are main problem and play a major role in the hematologic genetic disorders. In this paper, we propose different approaches to discover orthologs of homologous hereditary diseases of the hematological system and find the evolutionary relationship between hereditary genetic diseases of the hematological system by adjoining the joining method of contiguous merging trees.Â